Effects of differents parasiticides on the biliary tract. - Fernández Naone, Gonzalo; Bianchi, Gerardo; Palacios, Gerardo; Piazze, Alvaro; Keuchkerián, Sandra (Cirugía del Uruguay, 1988)
The effect of three differents hydatidic cyst parasili· cides on the biliary tract and the liver of the rat is stu• died, hydrogen peroxide, sodium chloride solution and formaldehyde. Results are evaluated through the pathology study done at seventh and fourteenth day, conclusions are shown.